Restructuring for service business development: insights from a machine tool manufacturer. (14th August 2019) - Kamp, Bart
This article considers how a manufacturing company redesigns its organisation to take advantage of service business opportunities. It also looks at the role played in this process by company agents other than top management. Analysis of the company's initial conditions and subsequent change dynamics is based on action research. Findings are that actors from lower hierarchical levels within the organisation do not necessarily behave as opponents to change and can enhance the adoption of organisational solutions in favour of servitisation. In addition, it finds that such organisational solutions can build simultaneously upon a dual product/service approach across the firm, a reconsideration of front-line and back-end functions, and upon semi-detached or stand-alone structures. Consequently, it asserts that senior directors can try to build upon change agents inside their companies to develop servitisation-friendly organisational structures. Similarly, it contends that organisational solutions that servitising companies implement can contain both internal and external elements.